MEASUREMENT OF COOPERATIVE PRODUCTIVITY LEVEL: IN ACEH: THE MALMQUIST INDEX APPROACH - Azhari Azhari; Kamaruddin Kamaruddin (Universitas Padjadjaran, 2021)
Based on article 33 of the 1945 constitution, cooperatives are the backbone of Indonesia national economy. However, the hopes of cooperative to become the locomotive of the Indonesian economy are still far from expectation. the purpose of this research to measure the level of productivity and efficiency of cooperatives by using Data Envelopment Analysis and Malmquist Index analysis tools. Input variables used are own capital, external capital, labor, and members, while the output variable is turnover and the surplus (SHU) cooperatives from 23 districts/cities in Aceh from 2014 to 2016. Test results show that cooperatives that have an index value-efficient only in seven districts / cities, while in terms of productive cooperatives in Aceh as many as 14 districts/cities in Aceh. It is expected that policymakers in fostering and empowering cooperatives in Aceh, both from the government and cooperative management and other stakeholders, can improve cooperative performance through cooperative education and training for cooperative human resources, provide a conducive business climate and provide capital loans with easy schemes for cooperative. The limitation of this study is that the types of cooperatives used are cooperatives as a whole not classifying cooperative types. Testing the level of efficiency and productivity of cooperatives with various types of cooperatives that exist is a special attraction The objective is in the third line, the method is in the fourth line, the results and discussion are in the sixth line, the conclusions and suggestions are on the eighth line and so on.